Clinical Characteristics and Outcomes Until 2 Years of Age in Preterm Infants With Typical Chest Imaging Findings of Bronchopulmonary Dysplasia: A Propensity Score Analysis - Ruan, Qiqi; Wang, Jianhui; Shi, Yuan (Frontiers in Pediatrics, 2021)
Objective: The goal of the current study was to assess the associations of typical chest imaging findings of bronchopulmonary dysplasia (BPD) in preterm infants with clinical characteristics and outcomes until 2 years of age. Method: This retrospective cohort study enrolled 256 preterm infants with BPD who were admitted between 2014 and 2018. A propensity score analysis was used to adjust for confounding factors. The primary outcomes were the severity of BPD, home oxygen therapy (HOT) at discharge and mortality between 28 days after birth and 2 years of age. A multivariate logistic regression analysis was performed to identify related variables of mortality. Results: Seventy-eight patients with typical chest imaging findings were enrolled, of which 50 (64.1%) were first found by CXR, while 28 (35.9%) were first found by CT. In addition, 85.9% (67/78) were discovered before 36 weeks postmenstrual age (PMA) (gestational age [GA] < 32 weeks) or before 56 days after birth (GA > 32 weeks). After propensity score matching, the matched groups consisted of 58 pairs of patients. Those with typical imaging findings had a remarkably higher mortality rate (29.3 vs. 12.1%, p = 0.022, OR 3.021), higher proportion of severe BPD (32.8 vs. 12.1%, p = 0.003, OR 4.669) and higher rate of HOT at discharge (74.1 vs. 46.6%, p = 0.002, OR 3.291) than those without typical imaging findings. The multivariate logistic regression analysis showed that typical imaging findings ≤ 7 days and typical typical imaging findings >7 days were independent risk factors for mortality in preterm infants with BPD (OR 7.794, p = 0.004; OR 4.533, p = 0.001). Conclusions: More attention should be given to chest imaging findings of BPD, especially in the early stage (within 7 days). Early recognition of the development of BPD helps early individualized treatment of BPD. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT04163822.